Analytical Hierarchy Process Method of Prosthetic and Orthotic Materials for Patient Needs - Nurkholiza, Rahmiyana; Beng, Jap Tji; Wasino, Wasino; Tiatri, Sri; Sam, Toong Hai; Anolin, Ann G.; Castillo, Sheryll Ann M.; Dinatha, Vienchenzia Oeyta Dwitama (STMIK Banjarbaru, 2025)
This study highlights the importance of optimising assistive devices for people with disability, as the law says in Law No. 8 of 2016. Ligar Mandiri Prosthetics and Orthopaedics Clinic offer related services, where choosing the right materials is getting more complicated because of fast tech advances and lots of options like carbon fibre, plastic, and titanium. This study aims to develop a Decision Support System (DSS) to assist practitioners in selecting materials based on quality, cost, and production time criteria. The alternatives evaluated include local, semi-imported, and imported materials. Using the Analytic Hierarchy Process (AHP) method, the analysis shows that imported materials received the highest ranking (0.54708), followed by local materials (0.24157) and semi-imported materials (0.21155). The DSS developed in this study has enhanced the accuracy, efficiency, and transparency of decision-making, thereby supporting practitioners in providing effective and reliable prosthetic and orthotic solutions.